Analysis on Force Transmission Characteristics of Two-Legged Shield Support under Impact Loading - Qing-liang Zeng; Zhao-sheng Meng; Li-rong Wan; Cheng-long Wang (Shock and Vibration)
To study the load transfer characteristics of a two-legged shield powered support, a numerical simulation model of the support was established using the multibody dynamics software ADAMS. The model took full account of the hydraulic-elastic deformation characteristics of the support, as a series spring-damper system was used to replace the leg and the equilibrium jack. The canopy, goaf shield, lemniscate bars, and equilibrium jack are equivalent to flexible bodies. The setting force of the leg was provided by the preload of the equivalent spring, the static roof load was simulated using a slope signal, and the impact load was simulated using a step signal. Using the model, the impact and excitation effects of each hinge joint of the support were analyzed under different impact load conditions across the canopy. The results show that the location of the impact load affects the force transmissions of all hinge points of the support. Both the impact effect and the excitation effect are at a minimum when the impact force is located near the leg action line. These results are useful for the adaptive control and structural design optimization of the support.